Who Creates Stable Jobs? Evidence from Brazil - Peter Brummund; Laura Connolly (Institute of Labor Economics (IZA), 2018)
Recent research shows that start-ups are important for job creation, but these firms are also inherently volatile. We use linked employer-employee data to examine the relative importance of firm age and firm size for job creation and destruction in Brazil. Firm age is a more important determinant of job creation in Brazil than firm size; young firms and start-ups create a relatively high number of jobs. However, young firms are also more likely to exit the market and have higher levels of employment volatility. We, therefore, condition the job creation analysis on job stability. Young firms and large firms create relatively more stable jobs in Brazil.
Keywords: L25; J23; J63; 330; job creation; job stability; Brazilian labor market